New combinations and new names in Myrcia for West Indian species previously included in Calyptranthes (Myrtaceae) - Campbell, Keron C. St. E.; Acevedo-Rodríguez, Pedro; Acosta, Zenia; Commock, Tracy; Lima Lourenço, Ana Raquel; Peguero, Brigido; Samra, Kate; Lucas, Eve J. (Phytotaxa, 2019)
132 currently accepted names for West Indian region and continental American Calyptranthes species are here transferred to Myrcia. Geographic distributions are also documented for each species.